Association between television viewing and overweight and obesity among women of reproductive age in Timor-Leste: evidence from the demographic health survey 2016 - Talukder, Animesh; Gupta, Rajat Das; Hashan, Mohammad Rashidul; Haider, Shams Shabab; Sajal, Ibrahim Hossain; Sarker, Malabika (BMJ open, 2021)
Objective This study aimed to assess the possible relationship between television viewing and overweight and obesity among Timorese women of reproductive age. - Methods This cross-sectional study analysed the Timor-Leste Demographic and Health Survey 2016 dataset. A weighted sample of 11 398 Timorese women aged 15-49 years was chosen using a two-stage stratified random sampling technique. Asian criteria-based body mass index (BMI) cut-offs were used to define overweight (BMI 23.0 to <27.5 kg/m2) and obesity (BMI ≥27.5 kg/m2). Frequency of TV viewing was categorised into three groups: (1) not at all, (2) less than once a week and (3) at least once a week. Multilevel ordered logistic regression was performed to identify the correlates of overweight and obesity. Both crude and adjusted odds ratios (AOR) along with a 95% CI were calculated to show the strength of association. - Results Among 11 398 respondents, 19.4% were overweight or obese (overweight: 15.7% and obese: 3.8%). Although about half of the respondents reportedly did not watch TV at all, just over two-thirds watched TV at least once a week. Women who watched TV at least once a week were found to have 1.3 times the odds of being overweight or obese compared with those who never watched TV (AOR: 1.3, 95% CI: 1.1 to 1.5; p<0.001). However, when stratified by settlement type, the statistical significance stood for the rural women only (AOR: 1.5, 95% CI: 1.2 to 1.8; p<0.001), after adjusting for the covariates. - Conclusion Watching TV at least once a week was found to be a significant correlate of overweight and obesity in rural Timorese women of reproductive age. Further studies need to be undertaken to assess physical activity, sedentary and dietary patterns to clarify the possible mechanism through which TV viewing may influence BMI in those groups.
Gesehen am 12.05.2022